2017
DOI: 10.1080/09638288.2016.1276972
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ai Chi on balance, quality of life, functional mobility, and motor impairment in patients with Parkinson’s disease

Abstract: Our results suggest that an Ai Chi exercise program improves balance, mobility, motor ability, and quality of life. In addition, Ai Chi exercise was more effective as an intervention than land-based exercise in patients with mild to moderate Parkinson's disease. Implications for rehabilitation Ai Chi exercises (aquatic exercises) may help improve balance, functional mobility, health-related quality of life, and motor ability in patients with mild to moderate Parkinson's disease more efficiently than similar la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 44 publications
1
76
0
9
Order By: Relevance
“…One of the most recent trials introduced "Ai Chi" exercises, a Japanese aquatic therapy, to the rehabilitation program for mild and moderate PD patients [114]. After five weeks of training, an improvement of mobility, balance, motor ability and quality of life was observed compared to the group which followed a land-based program [114]. This study suggests that this discipline, instead of the traditional exercises, might have a positive effect reducing PD symptoms.…”
Section: Sirtuins In Neurodegenerative Disorders Of Interest For Rehamentioning
confidence: 79%
See 1 more Smart Citation
“…One of the most recent trials introduced "Ai Chi" exercises, a Japanese aquatic therapy, to the rehabilitation program for mild and moderate PD patients [114]. After five weeks of training, an improvement of mobility, balance, motor ability and quality of life was observed compared to the group which followed a land-based program [114]. This study suggests that this discipline, instead of the traditional exercises, might have a positive effect reducing PD symptoms.…”
Section: Sirtuins In Neurodegenerative Disorders Of Interest For Rehamentioning
confidence: 79%
“…A large body of evidence suggest for a significant improvement of PD symptoms after physical activity. One of the most recent trials introduced "Ai Chi" exercises, a Japanese aquatic therapy, to the rehabilitation program for mild and moderate PD patients [114]. After five weeks of training, an improvement of mobility, balance, motor ability and quality of life was observed compared to the group which followed a land-based program [114].…”
Section: Sirtuins In Neurodegenerative Disorders Of Interest For Rehamentioning
confidence: 99%
“…Given that PSP shares several symptoms and clinical phenotypes overlapping PD, rehabilitative interventions were borrowed from those applied in PD, to improve mainly balance and gait impairment. With regard to this aspect, a growing number of studies have reported that PhyE [13‐15,34], and treadmill training [16] are efficacious in the rehabilitation of patients with PD. In particular, it has been reported that PhyE improves strength, posture, and gait in PD patients [15,35‐37].…”
Section: Discussionmentioning
confidence: 99%
“…So far, experimental pharmacologic strategies by inhibitors of glycogen synthase kinase 3 (GSK‐3), which has a key role in tau hyperphosphorylation, as well as substances stabilizing microtubules (davunetide) have been ineffective [10‐12]. A growing number of studies have reported the effectiveness of rehabilitation in PD, in particular the effect of physical exercises [13‐15], and weight‐supported treadmill training [16] in improving gait parameters and balance. Little has been published about rehabilitation interventions in PSP, and whether rehabilitative interventions might produce benefit is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The median score for methodological quality using the PEDro scale was seven out of ten (IQR 7,7). Eight of the 11 included studies scored between seven and eight implying moderate quality, [28][29][30][31][62][63][64][65] with a high risk of bias recorded for blinding of therapists and subjects, and intention to treat analysis (Table II).…”
Section: Methodological Qualitymentioning
confidence: 99%